2021
DOI: 10.1016/j.actpsy.2021.103423
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health behaviours intended to prevent spread of respiratory pathogens that have pandemic potential: A rapid review

Abstract: Effective public health messages to encourage behaviours to reduce the spread of COVID-19 should be informed by existing research that identifies the factors that are associated with these preventive behaviours. This rapid review summarises the existing research on the determinants of behaviours that aim to prevent the spread of COVID-19. The review focuses on the body of research (excluding research conducted with health care workers) that was produced in the context of viruses other than SARS CoV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 57 publications
0
16
0
5
Order By: Relevance
“…In the study, it is reported that working students are less likely to wear the N95 respirator compared to those who only study. In this regard, previous studies reported that the use of masks is greater in the unemployed population in relation to those who perform some work activity (11)(12) . This finding shows that those who work and study live in a situation of greater vulnerability, as they cannot buy a more expensive product such as the N95 respirator because they cannot afford it (25) .…”
Section: Discussionmentioning
confidence: 91%
“…In the study, it is reported that working students are less likely to wear the N95 respirator compared to those who only study. In this regard, previous studies reported that the use of masks is greater in the unemployed population in relation to those who perform some work activity (11)(12) . This finding shows that those who work and study live in a situation of greater vulnerability, as they cannot buy a more expensive product such as the N95 respirator because they cannot afford it (25) .…”
Section: Discussionmentioning
confidence: 91%
“…En el estudio, se reporta que los estudiantes que trabajan tienen menor probabilidad de usar el respirador N95 en comparación con los que únicamente se dedican a estudiar. Al respecto, estudios previos han reportado que el uso de mascarilla es mayor en la población desempleada en comparación con los que realizan alguna actividad laboral (11)(12) . Este hallazgo evidencia que quienes laboran y estudian, viven una situación de mayor vulnerabilidad, debido a que no se encuentran en condiciones de comprar un producto de mayor costo como el respirador N95 porque carecen de capacidad de pago (25) .…”
Section: Discussionunclassified
“…La decisión de usar la mascarilla está determinada por múltiples factores socio-demográficos y comunitarios (8) . Estudios realizados en pandemias virales señalan que existe consenso en que las mujeres, los que reportan tener estado civil casado y los que viven en zonas urbanas reportan mayor uso de mascarilla (9)(10) ; sin embargo, existe discrepancia entre la asociación de la edad, el grado de instrucción y el nivel de ingresos económicos con el uso de estos dispositivos (11)(12) . En cuanto a las creencias y emociones, coinciden en señalar que existe correlación positiva entre la preocupación, miedo, estrés, percepción de la susceptibilidad, severidad y eficacia con el uso de las mascarillas (9)(10)13) ; pero, a su vez, señalan que existe contradicción con la percepción de riesgo (14)(15) .…”
Section: Introduciónunclassified
See 1 more Smart Citation
“…2 These measures not only varied geographically, but they were also quite fluid in terms of time and perplexing, with many controversies on what is actually effective (e.g. Cheng, 2020); and most importantly, they translated the behaviour in daily encounters in which many people might not be sure about what is appropriate in a particular situation or even actively oppose the new pandemic etiquette in diverse ways (Hanratty et al, 2021). some cases, research participants, informed about safety rules through information sheets and briefed during phone conversations arranging the face-to-face interviews, refused to wear a mask once the interview started.…”
Section: Doing the Interviewmentioning
confidence: 99%